2011
DOI: 10.1177/0021998311424625
|View full text |Cite
|
Sign up to set email alerts
|

Rotary ultrasonic machining of carbon fiber-reinforced plastic composites: using cutting fluid vs. cold air as coolant

Abstract: Drilling is involved in many applications of carbon fiber-reinforced plastic (CFRP) composites. Rotary ultrasonic machining (RUM) has been successfully employed to drill holes in CFRP using either cutting fluid or cold air as coolant. However, there are no reported studies to compare the results in RUM of CFRP using these two types of coolant. This article, for the first time, presents an experimental study to compare cutting force, torque, surface roughness, burning of machined surface, and tool wear in RUM o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 30 publications
6
45
0
1
Order By: Relevance
“…Cutting force is one of the main output variables, since it is associated with tool wear, cutting temperature, surface roughness, and torque [21,22]. Figure 6a shows a comparison of cutting force between intermittent and continuous RUM.…”
Section: Effects On Cutting Forcementioning
confidence: 99%
“…Cutting force is one of the main output variables, since it is associated with tool wear, cutting temperature, surface roughness, and torque [21,22]. Figure 6a shows a comparison of cutting force between intermittent and continuous RUM.…”
Section: Effects On Cutting Forcementioning
confidence: 99%
“…Power consumption of the spindle motor was calculated by Effects of ultrasonic power on other output variables (including cutting force, torque, and surface roughness) had been studied [Cong et al, 2011c]. When ultrasonic power increased from 0% to 80%, cutting force and torque decreased.…”
Section: Measurement Proceduresmentioning
confidence: 99%
“…Feasible regions in RUM of CFRP using cold air as coolant have been identified [Cong et al 2011b]. A comparison of RUM of CFRP using cold air and cutting fluid has been made [Cong et al 2011c]. These studies have shown that ultrasonic vibration in RUM can reduce cutting force, torque, cutting temperature, workpiece delamination, and tool wear.…”
Section: Introductionmentioning
confidence: 99%
“…Ra also can be improved by applying different coolant delivery modes (continuous mode and intermittent mode) and different coolant type (cold air or cutting fluid) (Cong et al, 2011;Li et al, 2005b). Tool slots have different influences on surface roughness for different workpiece material.…”
Section: Experimental Investigations On Surface Roughnessmentioning
confidence: 99%
“…It is reported that UVAG has six to ten times higher MRR than traditional grinding , and it is about ten times faster than ultrasonic machining (USM) (Cleave, 1976). Tool pressure and torque in UVAG are low (Cleave, 1976;Cusumano et al, 1974;Cong et al, 2011Cong et al, , 2013aCong et al, , 2012cCong et al, , 2012d: lower pressure is especially helpful when drilling small holes, deep holes, or adjacent holes with thin dividing walls (Cleave, 1976). UVAG also has reduced edge chipping, breakout and damage (Cleave, 1976).…”
Section: Introductionmentioning
confidence: 99%